0662 Hybrid Therapies to Improve Sleep Apnea Management. (27th May 2020) - Pogach, M; Cohn, V; Thomas, R J
Abstract: Introduction: A one-size fits all approach to sleep apnea management, as is promoted by insurance requirements, pervades the field of sleep medicine but does not address individual differences in disease phenotype or treatment tolerance or attempt to achieve meaningful targets for adherence or disease optimization. Continuous positive airway pressure (CPAP) is considered to be the gold standard treatment for sleep apnea, yet CPAP nonadherence rates remain high (estimates at > 30%) while usage goals (at least 4 hours/night) and therapeutic success targets (machine detected AHI < 5) allow for substantial residual disease to persist. Hybrid therapy, combining mandibular advancement device (MAD) and positive airway pressure (PAP), has demonstrated additive effects on lowering the AHI, ODI, and therapeutic PAP pressure in severe OSA patients with pressure intolerance. This analysis explores the impact of hybrid therapy on treatment adherence and optimization, and identifies patient and data characteristics suggestive of benefit from combined therapies. Methods: In a retrospective analysis, we reviewed the demographic data, medical histories, home sleep test, diagnostic and therapeutic attended polysomnography results, and PAP device settings and data (including usage, leak, residual event index, and waveforms) pre-and post-hybrid approach, in patients treated with hybrid therapy in our multidisciplinary academic sleep disorders clinic from 2014-2019. Results: Hybrid therapies utilized include simultaneous (MAD worn together with PAP), alternating (MAD and PAP separately over parts of or on alternating nights), and anchoring (MAD to maintain mouth closure and jaw stability to minimize leak). Preliminary analysis (N=30) shows that hybrid therapy compared to PAP alone improves PAP adherence, lowers residual AHI, minimizes periodic breathing, reduces aerophagia, and lowers therapeutic PAP pressure in these patients. Patient and data characteristics suggestive of benefit include high loop gain sleep apnea, complex apnea, mouth breathing, and position dominance. Conclusion: Individualizing treatment by combining therapies can result in improved PAP tolerance, usage, and disease control. Support: